АКТУАЛЬНЕ ПИТАННЯ ЩОДО РОЗВИТКУ ПРАВОВОЇ ДУМКИ ПРО УНІТАРНУ ФОРМУ ДЕРЖАВИ: ТЕОРЕТИКО-ПРАВОВИЙ АСПЕКТ - Сутко, Михайло (SUPREMANCE OF LAW, 2018)
This article explores topical issues of development of legal opinions on a unitary form of the state. The experience of developing a unitary state of a single, simple, unitary state has not lost its relevance, because in today’s developed society, most states have a unitary form of state structure.